Seleksi dan Peringkat Kelulusan KIP Kuliah di Sumut I dengan ID3 dan Promethee - Luhut Tony Sihotang; Alfonsus Situmorang; Margaretha Yohanna (Universitas Methodist Indonesia, 2024)
The selection of recipients of the Indonesia Smart Card (KIP) Lecture Program at the Dr. Sofyan Tan Aspiration House, North Sumatra, faces challenges in assessing the eligibility of prospective students efficiently and objectively. This research develops an artificial intelligence-based decision support system using the Iterative Dichotomizer 3 (ID3) algorithm and the PROMETHEE method. The ID3 method is applied in the initial administrative selection stage based on criteria such as parents' income, number of siblings, and home ownership, with an accuracy rate of 87.50%. Furthermore, the PROMETHEE method is used to rank prospective recipients who pass the initial selection according to the quota at the Methodist University of Indonesia. This hybrid system improves speed, accuracy, and transparency in selection, and supports a more equitable allocation of KIP Kuliah. This research contributes to the development of decision support systems for scholarship selection and can be used as a reference for future education policies.